The untold story: June´s case study - Gomez Amich, Maria (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Undoubtedly, Secret Intelligence Services’ stories are based on people. And so is this article, which presents a new insight through a unique testimony from a narrative interview of an MI6 veteran linguist whose existence was kept highly guarded for more than 40 years. Drawing on first-hand testimony and a range of historical publications, this article presents a thematic study of key details about the decoding, translating and indexing activities performed by MI6 veterans. It is interwoven with data collected from a three-and-a-half hour interview which was subsequently manually analysed according to keywords and themes. Owing to the small corpus, this article does not seek to draw any conclusions but rather to serve as a tribute to all those who worked with languages at MI6 sections during World War II.